RETRACTED: Influence of fillers on the formation of properties of bitumen matrices for the construction industry - Konoreva O. V.; Katrich Ya. M. (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001